PENGEMBANGAN MEDIA FILTER AIR SABUT KELAPA UNTUK MENINGKATKAN KEPEDULIAN LINGKUNGAN SISWA PADA MATERI TINDAKAN PENGHEMATAN AIR PEMBELAJARAN IPAS KELAS III SDN 060853 - Heppy Rani Maryana Sinaga; Zainuddin Zainuddin (STKIP Subang, 2026)
This research aims to develop a coconut fiber water filter to increase students' environmental awareness in the water conservation lesson for third-grade science students at SD Negeri 060853. This research was motivated by students' low environmental awareness regarding water cleanliness, wasteful water use, and a learning process that tends to be theoretical and lacks hands-on experience. Therefore, concrete, contextual learning media that utilizes natural materials in the surrounding environment are needed to encourage students to be more active in learning. The research used Research and Development (R&D) with the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects were 20 third-grade students at SD Negeri 060853.Data collection techniques were observation, interviews, questionnaires, and documentation. The research instruments consisted of validation sheets from media experts and subject matter experts, a practicality questionnaire, and a student environmental awareness questionnaire. Data analysis was conducted using descriptive quantitative methods using percentages and NGain calculations. The results showed that the Coconut Fiber Water Filter media achieved a validity score of 86.6%, categorized as very valid. Its practicality was categorized as very practical, at 87.2%. The media's effectiveness was demonstrated by an increase in students' environmental awareness, from 51% in the pretest to 91.2% in the posttest, with an N-Gain of 0.82, categorized as high. Therefore, the Coconut Fiber Water Filter media is considered valid, practical, and effective for use in science learning to increase students' environmental awareness.